Cosmopolitan Citizenship
VIII, 218 p.
Keywords: An original discussion and analysis of the meaning and scope of citizenship. The book examines the concept of citizenship in the light of normative ethical and political arguments as to the possible costs and benefits to political order, community, rights and participation of opting either for a cosmopolitan or a bounded citizenship ideal. As well as putting the concept of cosmopolitan citizenship into question, this book raises fundamental issues as to the adequacy of the current conceptual resources of political and international theory.